Understanding risks and consequences of pathogen infections on the physiological performance of outmigrating Chinook salmon. Issue 1 (21st January 2022) - Mauduit, F; Segarra, A; Mandic, M; Todgham, A E; Baerwald, M R; Schreier, A D; Fangue, N A; Connon, R E
Abstract: The greatest concentration of at-risk anadromous salmonids is found in California (USA)—the populations that have been negatively impacted by the degradation of freshwater ecosystems. While climate-driven environmental changes threaten salmonids directly, they also change the life cycle dynamics and geographic distribution of pathogens, their resulting host-pathogen interactions and potential for disease progression. Recent studies have established the correlation between pathogen detection and salmonid smolt mortality during their migration to the ocean. The objective of the present study was to screen for up to 47 pathogens in juvenile Chinook salmon ( Oncorhynchus tshawytscha ) that were held in cages at two key sites of the Sacramento River (CA, USA) and measure potential consequences on fish health. To do so, we used a combination of transcriptomic analysis, enzymatic assays for energy metabolism and hypoxia and thermal tolerance measures. Results revealed that fish were infected by two myxozoan parasites: Ceratonova shasta and Parvicapsula minibicornis within a 2-week deployment. Compared to the control fish maintained in our rearing facility, infected fish displayed reduced body mass, depleted hepatic glycogen stores and differential regulation of genes involved in the immune and general stress responses. This suggests that infected fish would have lower chances of migration success. In contrast, hypoxia and upper thermal tolerances were not affected by infection, suggesting that infection did not impair their capacity to cope with acute abiotic stressors tested in this study. An evaluation of long-term consequences of the observed reduced body mass and hepatic glycogen depletion is needed to establish a causal relationship between salmon parasitic infection and their migration success. This study highlights that to assess the potential sublethal effects of a stressor, or to determine a suitable management action for fish, studies need to consider a combination of endpoints from the molecular to the organismal level.